Physiological and intestinal microbiota responses of sea cucumber Apostichopus japonicus to various stress and signatures of intestinal microbiota dysbiosis - Cui, Liang; Xie, Yumeng; Luo, Kai; Wang, Mingyang; Liu, Longzhen; Li, Changlin; Tian, Xiangli (Frontiers in Microbiology, 2024)
Identifying the signatures of intestinal dysbiosis caused by common stresses is fundamental to establishing efficient health monitoring strategies for sea cucumber. This study investigated the impact of six common stress experienced frequently in aquaculture on the growth performance, intestinal homeostasis and microbiota of sea cucumber, including thermal (23°C), hypoosmotic (22‰ salinity), ammonium (0.5 mg/L NH4+-N), and nitrite (0.25 mg/L NO2−-N) stress exposure for 30 days, as well as starvation and crowding (6 kg/m3 density) stress exposure for 60 days. Results demonstrated that all stress led to reduced growth performance and digestive capacity of sea cucumber, along with varying degrees of oxidative stress and immune responses. Various stresses significantly altered the diversity, community structure (except for crowding stress), and composition of intestinal microbiota. The ratios of Bacteroidota: Proteobacteria (B: P) and Firmicutes: Proteobacteria (F: P) declined markedly compared to the control. Potentially pathogenic bacteria of Shewanellaceae, Vibrionaceae, and Moraxellaceae significantly increased under crowding, ammonium, and nitrite stress, respectively, whereas beneficial microbes of Achromobacter and Rhodobacteraceae were, respectively, enriched under hypoosmotic and starvation stresses. The complexity and stability of microbial ecological networks were further altered by these stresses. KEGG predictions revealed the reduced functional pathways of intestinal microbiota involved in host immunity under different stresses. Correlation analysis further confirmed a strong link between microbiota response and host immunity under different stresses. The increased abundance of Verrucomicrobia species could also be identified as the sensitive indicator for diagnosing whether the host was under stressful pressure by random forest analysis.